Coincidence of drug induced liver injury and cholecystitis on human immunodeficiency virus patient with anti-tuberculosis treatment - Putra, Putu Arthana; Suryana, Ketut (International Journal of Advances in Medicine, 2022)
Tuberculosis (TB) is a serious health problem. Anti-TB treatment has good efficacy, but in some cases side effects can occur that can affect medication adherence and development of drug resistance. One of the serious side effects of anti-TB treatment is drug induced liver injury. We reported the case of a 56 year old male patient with TB-HIV confection who developed symptoms of hepatotoxicity after 3 weeks of intensive phase of anti-TB treatment.